The Impact of Fraud Awareness and Religiosity on Internal Control and Sustainable Financial Performance (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
Internal control is a crucial practice in ensuring the sustainable financial performance of the Community Health Centers and Regional General Hospitals, especially after becoming a Regional Public Service Agency. This study aims to empirically test the effect of internal control on sustainable financial performance moderated by fraud awareness and religiosity in Regional Public Service Agencies in the health sector in Indonesia. This investigation used a quantitative approach. The distribution of questionnaires served as the main source of data. The study focuses on Indonesia's BLUD health sector, which includes Community Health Centers and Regional General Hospitals. The head of the RSUD, the head of the Puskesmas, the finance department, midwives, nurses, and personnel are among the 160 respondents in the research data. WarpPLS version 7.0 is the statistical tool used in the structural equation model, partial least squares data analysis process. The findings demonstrated that internal control significantly improves BLUD's sustainable financial performance and that internal control's beneficial effects are amplified by fraud awareness and religiosity.